Suburban Area English Teachers’ Implementation of Distance Learning: Methods, Challenges, and Perceptions - Yusdiansyah, Brian Asprilla; Prayogo, Johannes Ananto; Laksmi, Ekaning Dewanti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study employs a multiple case study method and aims to investigate, discover, and describe the suburban area English teachers teaching methods during the distance learning, challenges which are faced by the teachers, how the teachers solve those challenges, and the teachers’ perceptions towards the implementation of distance learning. The findings revealed that the teachers use direct teaching and more focused on utilizing the technology. Some of those challenges are mainly caused by the students ‘conditions. In order to obtain more genuine and valid results, a future study with better research instruments need to be conducted.